Percepção da equipe multiprofissional sobre o cuidado humanizado nas unidades de terapia intensiva de um hospital escola - Evangelista, Viviane Canhizares [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The experience gained in the context of Intensive Care Units (ICUs) awakens questions to topics related to humanized actions. ICUs are places for critical care, assisted by a skilled multidisciplinary team, under the best possible conditions. The team's responsibility extends beyond the technological and pharmacological interventions focused on the patient. It includes assessing the patient’s family needs, their degree of satisfaction on the offered care, preserving the integrity of the patient, believing that the humanization of care helps reduce the patient’s and family’s trauma, and guides the professionals involved to a less mechanized assistance. The aim of this study was to understand the meaning of humanized care among professionals in the Intensive Care Units of a teaching hospital, from the working experience of a multidisciplinary team. This is a field study, with an exploratory and descriptive qualitative approach; the National Humanization Policy (NHP) was used as theoretical framework, and the Content Analysis as methodological framework. The subjects were 24 multidisciplinary team professionals (nurses, physiotherapists, psychologists, nutritionists, doctors and social workers) working in Adult ICUs. Data collection occurred through semi-structured interviews, focusing on the main question: What is your experience in the development of humanized care with patients admitted to an ICU, working in multidisciplinary team '. In this study, the multidisciplinary team of 24 professionals had average age of 35 years, the majority being female and Catholic. These professionals had an average of 10 years from graduation, 6 years of working in the ICU, and 15 professionals worked in a single job. In the interviews, themes and units of meaning emerged. Theme 1 - Multidisciplinary Team and what facilitates humanized care: focusing in the practice of individualized care; understanding and contextualizing the ...

A experiência adquirida em contextos de Unidades de Terapia Intensiva (UTIs) desperta questionamentos sobre temas relacionados a ações humanizadas. As UTIs são locais destinados a cuidados críticos, assistidos por uma equipe multiprofissional qualificada, sob as melhores condições possíveis. A responsabilidade da equipe se estende para além das intervenções tecnológicas e farmacológicas focalizadas no paciente, inclui avaliação das necessidades dos familiares, grau de satisfação destes sobre os cuidados realizados, além da preservação da integridade do paciente, acreditando-se que a humanização da assistência auxilia a diminuir os traumas do paciente, da família e norteia os profissionais envolvidos para uma assistência menos mecanizada. O objetivo deste estudo foi compreender o significado do cuidado humanizado para profissionais das Unidades de Terapia Intensiva, a partir da vivência em equipe multiprofissional de um hospital escola. Foi um estudo de campo, exploratório e descritivo, com abordagem qualitativa; utilizou como base teórica a Política Nacional de Humanização (PNH) e metodológica, a Análise de Conteúdo. Os sujeitos foram 24 profissionais da equipe multiprofissional (enfermeiros, fisioterapeutas, psicólogos, nutricionistas, médicos e assistente social) atuantes em UTIs Adulto. A coleta de dados se deu por meio de entrevista semiestruturada, tendo como foco principal a questão norteadora: Como é a sua experiência no desenvolvimento do cuidar humanizado junto a pacientes internados na UTI, atuando em equipe multiprofissional?. Nos resultados deste estudo, os 24 profissionais da equipe multiprofissional, com idade média de 35 anos, sendo a maioria do sexo feminino e religião católica. O tempo médio de formação destes profissionais é de 10 anos, sendo 6 anos o tempo de atuação em unidade crítica e, 15 dos entrevistados, atuam em um único emprego. Na análise das entrevistas, emergiram ...
Keywords: Humanização na saúde; Pessoal da area médica; Unidade de tratamento intensivo; Hospitais de ensino; Relações humanas; Comunicação interpessoal; Interpersonal communication |5 DLC